Bigger fish in small pond: The interaction between foreigners' trading and emerging stock market returns under the microscope - Numan Ülkü; Enzo Weber (Osteuropa-Institut Regensburg, 2011)
This paper provides the first study of foreign investors' trading in a sizeable European emerging stock market, using a combination of daily and monthly complete data collected at the destination. It also introduces the structural conditional correlation (SCC) methodology to identify the contemporaneous interaction between foreign flows and returns. We show that global emerging market returns are an additional driver of foreign flows after controlling for global developed market returns. Foreigners do negative (positive)-feedback-trade with respect to local returns at the monthly (daily) frequency. SCC methodology shows that the standard assumption in the literature, that flows cause returns contemporaneously but not vice versa, is not justified, even at the daily frequency, making price impact estimates reported in previous literature questionable.
Keywords: G15; C32; 330; Foreign investors' trading in emerging stock markets; feedback trading; price impact; structural VAR; structural conditional correlation; Börsenkurs; Kapitalertrag; Wertpapierhandel; Portfolio-Investition; Kapitalimport; Aufstrebende Märkte; Aktienmarkt; Schätzung; Türkei; Südkorea; Taiwan